Increased Risk of Revision after ACL Reconstruction with Soft Tissue Allograft Compared to Autograft: Graft Processing and Time Make a Difference - Maletis, Gregory (Orthop J Sports Med, 2016)
OBJECTIVES: The use of allograft tissue for anterior cruciate ligament reconstruction (ACLR) remains controversial. Numerous meta-analysis and systematic reviews of small clinical studies have not found differences between autograft and allograft outcomes but large registry studies have shown an increased risk of revision with allografts. The purpose of this study was to compare the risk of aseptic revision between bone-patellar tendon-bone (BPTB) autografts, hamstring tendon autografts and soft tissue allografts. METHODS: A retrospective cohort study of prospectively collected data was conducted using an US ACLR Registry. A cohort of primary unilateral ACLR cases reconstructed with BPTB autografts, hamstring autografts and soft tissue allografts (from any site) was identified. Aseptic revision was the end point of the study. Type of graft and allograft processing methods (non-processed, <1.8Mrads with and without chemical processing (Allowash or AlloTrue methods), >1.8 Mrads irradiation with and without chemical processing, and chemical processing alone (BioCleanse)) were the exposures of interest evaluated. Time from surgery was evaluated as an effect modifier. All analyses were adjusted for age, gender, and race. Kaplan-Meier curves and Cox proportional hazard models were employed. Hazard ratios (HR), 95% confidence intervals (CI) are provided. RESULTS: The cohort had 14015 cases, 8924 (63.7%) were male, 6397 (45.6%) were White, 4557 (32.5%) cases used BPTB autograft, 3751 (26.8%) cases used soft tissue allograft and 5707 (40.7%) cases used hamstring autograft. The median age was 34.6 years-old (IQR 24.1-43.2) for allograft cases and 24.3 years-old (IQR 17.7-33.8) for hamstring autograft cases, and 22.0 years-old (IQR 17.6-30.0) for BPTB autograft cases. Compared to hamstring tendon autografts, an increased risk of revision was found in allografts processed with >1.8Mrads without chemical processing after 2.5 years (HR: 3.88 95%CI 1.48-10.12), and >1.8Mrads with chemical processing after only 1 year (HR: 3.43 95%CI 1.58-7.47) and with BioCleanse processed grafts (HR: 3.02 95%CI 1.40-6.50). Compared to BPTB autografts, an increased risk of revision was seen with hamstring autografts (HR: 1.51 95%CI 1.15-1.99) and BioCleanse processed allografts (HR: 4.67 95%CI 2.15-10.16). Allografts irradiated with <1.8 Mrads with chemical processing (HR: 2.19 95%CI 1.42-3.38) and without chemical processing (HR: 2.31 95%CI 1.40-3.82) had a higher risk of revision as did allografts with > 1.8Mrads without chemical processing after 2.0 years (HR: 6.30 95%CI 3.18-12.48) and >1.8 Mrads with chemical processing after 1 year (HR: 5.03 95%CI 2.30-11.0). Non-processed soft tissue allografts did not have a higher risk of revision when compared to hamstring or BPTB autografts. CONCLUSION: When soft tissue allografts are used for ACLR, both processing and time from surgery affect the risk of revision when compared to autografts. Tissue processing has a significant effect on the risk of revision surgery and that effect is most profound with more highly processed grafts and increases with time. Surgeons and patients need to be aware of the increased risks of revision with the various soft tissue allograft used for ACLR.